Analysis of QTL responsible for grain iron and zinc content in doubled haploid lines of rice (Oryza sativa) derived from an intra‐japonica cross - Jeong, O-Young; Lee, Jeom-Ho; Jeong, Eung-Gi; Chun, Areum; Bombay, Maurene; Banzon Ancheta, Melanie; Ahn, Sang-Nag (Wiley, 2020)
Quantitative trait loci (QTL) related to the grain iron and zinc contents of brown rice were mapped by using a doubled haploid population derived from an intra‐japonica cross between 'Hwaseonchal' and 'Goami 2'. QTL–QTL, background–QTL, and background–background interactions and candidate genes that affect grain iron and zinc contents were preliminarily identified. Twenty‐one iron‐ and zinc‐related QTL were found. The major‐effect QTL qFe7 and qZn7 provided the highest contribution to phenotypic variance for grain iron and zinc contents. The colocation of zinc‐ and iron‐related QTL on chromosomes 1, 4, 7 and 11 may account for the strong correlation between iron and zinc contents. A region on chromosome 7 and epistatic interaction between loci on chromosomes 2 and 10 affected iron content. qZn7 and qZn11.3 exerted additive effects on zinc content. Eleven iron‐ and zinc‐related candidate genes colocated with qFe7, qZn7 and the region on chromosome 7 with an additive effect on iron content. The major‐effect QTL identified here may be useful for breeding biofortified rice.